Vaksin Covid-19: Perdebatan, Persepsi dan Pilihan - Lula Asri Octafia (Universitas Muslim Maros, 2021)
The current Covid-19 pandemic has had an impact on the political, economic, social, cultural, defense and security aspects as well as the welfare of the Indonesian people. Therefore, effective fast steps are needed to break the chain of the spread of Covid-19. One way to prevent transmission of this virus is through vaccination efforts. While the existing literature focuses more on State policies, public responses related to the effectiveness and safety of vaccines, as well as hoax news related to vaccines, the related literature on vaccines and the choice of vaccine if any is still very limited, this article fills that gap. This qualitative research was carried out in Makassar, considering that Makassar is one of the metropolitan cities and many of its people has been vaccinated through Covid-19 vaccination programs. Data was collected using in-depth interview. Informants who participated in this study were people who had and had not carried out the Covid-19 vaccination. With a total of twenty-five people, they vary on the basis of age (between 18 and 29 years), sex (18 women and 7 men), and employment status (ten of them are students, employees, online shop owners, editors, musicians, painters, work odd jobs, and labor). The results show that the emergence of the Covid-19 vaccine has become the subject of public debate, many agreed and not a few refused to be vaccinated. This debate is due to differences in perceptions regarding the definition of the Covid-19 vaccine and the benefits of the vaccine itself. In terms of what type of vacciness they are used, there are three types of vaccines that are popularly used by our participants in this study, namely Sinovac, Astra Zeneca, and Moderna. Apart from the debate about the level of efficacy of each vaccine, the choice of vaccine is related to the level of efficacy, side effects and availability of the vaccine itself. It is argued in this article that whatever the effect of a particular vaccine, as long as the side effect is balanced by its efficacy, then the effect is not an issue.